2018
DOI: 10.1097/md.0000000000013392
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of small hepatocellular carcinoma: perfusion quantification and time-concentration curve evaluation using color-coded and quantitative digital subtraction angiography

Abstract: To explore the role of quantitative digital subtraction angiography (QDSA) in the diagnosis of small hepatocellular carcinoma (HCC).Between November 2015 and November 2017, all patients who underwent chemoembolization for HCC were retrospectively reviewed. Patients with tumors measuring more than 5 cm or evident post-processing imaging artifacts were excluded. Images were post-processed using the QDSA technique. Regions of interest were manually drawn on proper hepatic artery (as a reference), target HCC and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Other attempts have been made to develop an objective embolization endpoint using volumetric imaging. One, quantitative 4D transcatheter intra-arterial perfusion MRI, showed promise, however, lacks feasibility as it requires a complex and costly hybrid angiography/MR suite only available at selected institutions [18,19]. A recent study demonstrated the feasibility of using quantitative 4D-DSA to depict changes in hepatic arterial blood velocity during transarterial embolization in a swine model, but the method requires lengthy data acquisition times and greater amounts of iodinated contrast [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Other attempts have been made to develop an objective embolization endpoint using volumetric imaging. One, quantitative 4D transcatheter intra-arterial perfusion MRI, showed promise, however, lacks feasibility as it requires a complex and costly hybrid angiography/MR suite only available at selected institutions [18,19]. A recent study demonstrated the feasibility of using quantitative 4D-DSA to depict changes in hepatic arterial blood velocity during transarterial embolization in a swine model, but the method requires lengthy data acquisition times and greater amounts of iodinated contrast [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Low spatial resolution, long scanning time, and patient respiratory motion cause images to form artifacts easily. QDSA Accurately measure arterial blood flow and improve the detection rate of HCC in the background of cirrhosis (33).…”
Section: Mr Dce-mrimentioning
confidence: 99%